Predicting Stress: The Role of Romantic Relationship Satisfaction, Gratitude, Forgiveness, Emotional Intelligence - Mansimran, Kaur (My University, 2022)
The study focused on role of romantic relationship satisfaction, gratitude, forgiveness and emotional intelligence on perceived stress by using people between the age of 18 to 30 years who were in a romantic relationship. The sample consisted to 201 individuals. To measure stress Cohen perceived stress scale by Cohen (1988) was sued. To measure romantic relationship satisfaction relationship assessment scale by Hendrick SS (1988) was used. GQ-6 scale by McCullough et. al (2002) was used to measure gratitude. To measure forgiveness Heartland Forgiveness Scale by Thompson & Synder (2003) was used. TEIQUE-SF scale was used to measure trait emotional intelligence. Correlation and regression analysis were done to predict the effect of romantic relationship satisfaction, gratitude, forgiveness and emotional intelligence on perceived stress. It was found that there was significant negative relationship of relationship satisfaction, forgiveness and emotional intelligence on perceived stress.
Keywords: Emotional Intelligence; Forgiveness, Relationship Satisfaction